High-Efficiency Adsorption of Hexavalent Chromium from Aqueous Solution by Samanea saman Activated Carbon. (15th July 2022) - Niam, Achmad Chusnun; Fenelon, Ernso; Ningsih, Erlinda; Mirzayanti, Yustia Wulandari; Kristanti, Eka
Abstract : Heavy metal wastewater pollution has become an environmental and industrial challenge worldwide. Hexavalent chromium (Cr(VI)) is one of the most common forms of chromium metal. Hexavalent chromium pollution is a concern because it was hazardous and can accumulate in the tissues of living organisms and the environment. The adsorption method using activated carbon can be one of the methods to treat hexavalent chromium waste. This study selected Samanea saman as the activated carbon because it contains hemicellulose, lignocellulose, and lignin, which are the requirements for an excellent activated carbon. The study's objective is to analyze Samanea saman activated carbon (SSAC) to remove hexavalent chromium, measure the adsorption capacity, and determine the appropriate type of adsorption isotherm layer based on the maximum R 2 and minimum χ 2 values. The process of making activated carbon was activated using K2 CO3 through a pyrolysis process and using batch adsorption. The SEM results as characterization of SSAC depicted that the high pore was well developed. The optimal conditions for Samanea saman indicated high efficiency toward hexavalent chromium ions within the following process parameters; pH value 5, adsorbent dosage 5 g, and initial concentration 20 mg/L. The findings demonstrate that SSAC leads to the removal efficiency of hexavalent chromium being 99.90%, with the greatest adsorption capacity of 0.8949 mg/g. Based on the maximum R 2 and minimum χ 2 values, the most suitable adsorption isotherm model in SSAC was the Freundlich isotherm existing in the monolayer (R 2 = 0.999 ). The experimental results demonstrated that adsorption of Cr(VI) was well performed by SSAC. Thus, the SSAC material is an appropriate adsorbent for the removal of hexavalent chromium in the water and has the potential to be industrial applied.